TINJAUAN YURIDIS PERJANJIAN PERIKATAN JUAL BELI TANAH DENGAN TRANSAKSI PEMBAYARAN BERTAHAP - NI MADE SUNDARINI; I WAYAN SUWANDA (Universitas Mahasaraswati Mataram, 2020)
This study aims to determine the procedure for making land sale and purchase agreements with gradual payment transactions and to determine the legal strength of land sale and purchase agreements with gradual payment transactions.This research uses empirical normative legal research methods with a study approach based on statutory regulations, conceptual approaches, and case approaches. Types and sources of data used in this study are primary data and secondary data with data collection techniques through document study and interviews. The data obtained were analyzed by qualitative deductive.Based on the results of the research, the procedure for making a land sale and purchase agreement with a gradual payment transaction must carry out three stages, namely (1) the pre-contractual stage in the form of conforming the wishes of the parties based on the offer and acceptance, (2) the contractual stage in the form of signing the agreement, and (3) the post stage. contractual in the form of exercising the rights and obligations of the parties. A land sale and purchase agreement with a gradual payment transaction is a written agreement made in the form of an agreement deed, reciprocal in nature and is included in the nominaate agreement category, in which to make a sale and purchase agreement must fulfill the legal requirements of the agreement, namely agreement, skill, object of the agreement, and causa that is kosher. The sale and purchase agreement in stages is classified as an authentic deed that has formal evidentiary power and is made in the presence of an authorized public official, namely a notary